Forecasting the influence of monetary policy on the economy of the Republic of Kazakhstan based on the dynamic stochastic general equilibrium model - Ishuova, Zh. Sh. (Journal of Economic Research & Business Administration, 2015)
The article considers the stages of building dynamic stochastic general equilibrium (DSGE) model applied to the economy of Kazakhstan and evaluates the effectiveness of monetary policy in Kazakhstan.There are developed the concept of mathematical modeling for the economy of the Republic of Kazakhstan, collected and processed statistics of major economic indicators, created a dynamic model of the economy, implemented calculation algorithm of its trajectory, performed identification and verification of the model and also conducted number of analytical and predictive calculations.Microeconomic studies suggest that the average period of constant prices of the degree of price rigidity in 2-4 quarters. Regard to Kazakhstan is expected a higher value of this parameter by using the consumer price index as a measure of inflation because the prices of many essential goods are subject to administrative regulation, which could potentially lead to greater rigidity.